Inhalation of sevoflurane in the removal of post-labioplasty and palatoplasty stitches in uncooperative children patients - Ediyana Nuryadi; Harry Arifin Kaiin; Kirana Lina Gunawan (Universitas Padjadjaran, 2007)
The technique of behaviour management in medical treatment, especially in dental treatment, is needed to eliminate uncooperative children behaviour. The main factor influencing children behaviour is fear of painful that usually related to dental treatment. Children patients who will have their postlabioplasty and palatoplasty stitches removed have more sensitive condition, they cry when the dentist gives treatment. Using general anesthesia is a method to manage uncooperative children behaviour. Inhalational anesthesia is often used in general anesthesia and sevoflurane is a drug of choice. Sevoflurane has low solubility in blood, pleasant odor, nonirritating airway, and has a rapid induction of and recovery from anesthesia. Some researches indicate that sevoflurane gives more calm condition and can be used as a sufficiently ideal induction and maintenance of anesthesia in children. Sevoflurane can therefore made as alternative procedure in the removal of post-labioplasty and palatoplasty stitches.